Chemical composition and in vitro rumen fermentation kinetics of leaves and stems of Moringa oleifera and Leucaena leucocephala as potential feedstuffs for sheep - Hajer Ammar; Ahmed E. Kholif; Egon Henrique Horst; Mario E. de Haro Marti; Izabelle Auxiliadora Molina de Almeida Teixeira; Nawel Hlel; Tarek A. Morsy; Mahmoud Fahmy; Gouda A. Gouda; Iván Mateos; Secundino López; Mireille Chahine (Cogent Food & Agriculture)
This study aimed to evaluate the nutritive value of different vegetative parts of Moringa oleifera (leaves, stems and plant debris) and Leucaena leucocephala (leaves and dried pods after seed harvesting). Nutrient composition, secondary metabolites and kinetics of gas production (GP) from in vitro rumen fermentation were measured to investigate the adequacy of these materials as feed resources for ruminants. Leaves of M. oleifera had the highest (p < .001) crude protein content (22.9%), total polyphenols (336 mg gallic acid equivalents/g dry matter [DM]), flavonoids (158 mg quercetin equivalent/g DM), condensed tannins (2.26 mg catechin equivalents/g DM) and extraction yield (29.3%). Debris of M. oleifera showed the highest (p < .001) antioxidant activity. The pods and leaves of L. leucocephala showed the highest organic matter (OM; 94.5 and 92.7%, respectively), neutral detergent fiber (63.1 and 64.6%, respectively), acid detergent fiber (48.5 and 45%, respectively) and hemicellulose (14.6 and 19.6%, respectively). However, the leaves and stems of M. oleifera showed the highest (p < .001) asymptotic GP (152 and 147 mL/g DM incubated) and fractional rate of fermentation (0.168 and 0.146 per h) compared to the leaves and pods of L. leucocephala. Additionally, the highest (p < .001) OM digestibility (59.8%), metabolizable energy (8.32 MJ/kg DM), net energy (in terms of forage units for lactation or meat production) were observed with the leaves of M. oleifera. In conclusion, the concentration of nutrients differed between plants and within parts of the plant. Leaves of M. oleifera showed higher nutritive value than the stems and shed material. The pods of L. leucocephala showed higher nutritive value than its leaves.